Education Reaching Learners Beyond our Hallowed Halls. - Dorn, Brian (Communications of the ACM, 2011)
The article discusses the design of computer science courses, focusing on adults working in non-computer disciplines who also develop scripts or programs as part of their work. A series of studies on how to support the educational needs of such informally trained programmers is described, focusing on professional graphic and Web designers. The educational needs of this group is said to be largely under-served by existing academic institutions.